Counting the Cost of Diabetes in the Solomon Islands and Nauru. - Si Thu Win Tin; George Iro; Eva Gadabu; Ruth Colagiuri (PLoS ONE)
Aim To determine the costs associated with diabetes to governments, people with diabetes and their carers, and its impact on quality of life in two Pacific Island countries--the Solomon Islands and Nauru. Materials and methods This cross-sectional cost of illness study was conducted on 330 people with type 2 diabetes (197 from the Solomon Islands and 133 from Nauru) using a structured cost of illness survey questionnaire adapted from the Australian DiabCo$t study. Quality of life was measured by the EQ-5D Visual Analogue Scale. Results There were 330 respondents (50% female; mean duration of diabetes 10.9 years; mean age 52.6 years). The estimated annual national cost of diabetes incurred by the Solomon Islands government was AUD 12.8 million (AUD 281 per person/year) and by Nauru government was AUD 1.2 million (AUD 747 per person/year). The major contribution to the government costs was inpatient services cost (71% in the Solomon Islands and 83% in Nauru). Annual expenditure for diabetes was approximately 20% of the governments' annual health care expenditure. Considerable absenteeism and retirement from work due to diabetes was found. Conclusions This study found substantial public and personal costs associated with diabetes. The findings provide objective data on which health policy, funding and planning decisions about the prevention and control of diabetes in the Solomon Islands and Nauru can be reliably based and subsequently evaluated.